Smartphone-supported Positive Adjustment Coping Intervention (PACI) for couples undergoing fertility treatment: A randomised controlled trial - Franziska Kremer; Maren Schick; Sabine Roesner; Ariane Germeyer; Markus Moessner; Stephanie Bauer; Beate Ditzen; Tewes Wischmann (PLoS ONE, 2025)
Background Couples undergoing fertility treatment experience emotional stress. Meta-analyses show heterogeneous results regarding the effectiveness of psychosocial interventions on anxiety and depression. Objective The aim of this study was to reduce psychosocial stress (anxiety, depression) in infertile patients. In addition, pregnancy rates and perceived distraction as well as perceived subjective relief were determined. Methods In a two-arm RCT we used “Positive Adjustment Coping Intervention (PACI)”. Participants received the first of 13 daily text messages on their smartphones on the day on which the cryopreserved embryos were thawed or one day after oocyte aspiration. Patients in the PACI condition obtained daily positive adjustment statements and were asked to relate these to their personal situation at least twice a day. Patients in the comparison condition were given daily think tasks providing cognitive distraction. Anxiety and depression scores were assessed with ScreenIVF and perceived distraction as well as relief with an evaluation form. Results PACI did not reduce participant´s depressive scores measured with standardized questionnaire ( P < .007, N = 227), did not significantly change participant´s anxiety (N = 227), nor did it increase pregnancy rates (N = 191). PACI had a significant effect on subjective perceived distraction ( P = .005, N = 197) and on perceived relief ( P = .026, N = 197). Conclusion This is the first RCT to use modern media to test a simple positive adjustment cognition intervention in women and men who underwent fertility treatment. The low-dose psychosocial intervention apparently was not sufficient to reduce emotional distress during the waiting period between embryo transfer and pregnancy test. Preferably, psychosocial support for infertile individuals could be provided face-to-face to reduce the target variables depression and anxiety. However, PACI has a positive influence on perceived distraction and perceived relief. Trial registration ClinicalTrials.gov: NCT03118219 (July 9, 2019)